1991
DOI: 10.1007/bf02465218
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the phosphorus depletion zone in VA-mycorrhizal white clover in a calcareous soil

Abstract: To examine the influence of vesicular-arbuscular (VA) mycorrhizal fungi on phosphorus (P) depletion in the rhizosphere, mycorrhizal and non-mycorrhizal white clover (Trifolium repens L.) were grown for seven weeks in a sterilized calcareous soil in pots with three compartments, a central one for root growth and two outer ones for hyphae growth. Compartmentation was accomplished by a 30-/zm nylon net. The root compartment received a uniform level of P (50 mg kg -1 soil) in combination with low or high levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
132
1
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(153 citation statements)
references
References 14 publications
14
132
1
6
Order By: Relevance
“…The total EM increased with time and reached about 19 m g -1 in the substrate with +AMF plants at 90 DAT, in all P levels. These data are in agreement with previous works (Abbott et al, 1984;Schubert et al, 1987;Sylvia, 1988;Li et al, 1991), in which the total EM ranged from less than 1 to about 26 m g -1 .…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The total EM increased with time and reached about 19 m g -1 in the substrate with +AMF plants at 90 DAT, in all P levels. These data are in agreement with previous works (Abbott et al, 1984;Schubert et al, 1987;Sylvia, 1988;Li et al, 1991), in which the total EM ranged from less than 1 to about 26 m g -1 .…”
Section: Resultssupporting
confidence: 93%
“…It is notorious that mycorrhizal citrus have higher P concentrations than control plants (Peng et al, 1993;Melloni et al, 2000) but, in this case, only at 25 and 200 mg kg -1 P. In these cases, shoot P concentrations in +AMF plants were above the sufficiency level of 1.9 g kg -1 for citrus, whereas the -AMF plants remained below the deficiency level of 1 g kg -1 (Graham et al, 1997). The EM may be responsible for more than 75% of the plant P uptake (Li et al, 1991). Based on the specific P uptake rate it could be seen that similar values were achieved by roots of +AMF plants, at the two lowest P levels.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The role of AMF in plant nutrition is likely to be important even when plants are genetically modified with other traits, such as root exudation of citrate (Lopez-Bucio et al 2000;Zhu et al 2001). The beneficial effects of AMF are due mainly to the ability of mycorrhizal fungal hyphae to acquire P well beyond the limits of the rhizosphere depletion zone (Li et al 1991). It has been widely reported that responsiveness to (or dependency on) mycorrhizal colonisation, in terms of improved growth and/or P uptake, varies between crop cultivars (Krishna et al 1985;Koide et al 1988;Bryla and Koide 1990;Rao et al 1990;Mercy et al 1990;Baon et al 1993;Hetrick et al 1993;Khalil et al 1994;Hetrick et al 1995).…”
Section: Introductionmentioning
confidence: 99%